Influence Of Individual Motivation, Family Support And Social Environment To Increase The Success Of Rehabilitation In The Working Area Of The Nasional Narcotics Agency Of South Sulwesi Province - Aljauzi Amri, Ibnul; Tamsah, Hasmin (Jurnal Mirai Management, 2016)
ABSTRACT This research aims to analyze (1) Influence of Motivation, (2) Influence of Family Support, (3) Influence of Social Environment to improvement of Rehabilitation Success, (4) Influence Individual Motivation, Family Support, Social Environment to improvement of Rehabilitation success. This study uses primary data with the number of respondents as much as 100, Sample are participants of Rehabilitation who are following the post-rehabilitation Assessment. The results of this study indicate that (1) there is Influence between Individual Motivation to Increasing Success of Rehabilitation, (2) The Influence between Family Support to Increasing Success of Rehabilitation, (3) No Significant Influence between Social Environment to Increasing Success of Rehabilitation, (4) ) The existence of Influence between Individual Motivation, Family Support, Social Environment to increase the success of Rehabilitation. Keywords: Individual Motivation, Family Support, Social Environment, Rehabilitation